Penerapan Kurikulum Merdeka Dalam Mengatasi Krisis Pembelajaran (Learning Loss) Pada Mata Pelajaran Pendidikan Agama Islam Kelas X di SMA Negeri Jenggawah Jember - Nafisa, Siti (Pendidikan Islam Pascasarjana IAIN Jember, 2023)
The learning loss that has occurred due to the COVID-19 pandemic has greatly impacted changes in education in Indonesia. To overcome this, a learning recovery policy is needed where the Merdeka Curriculum is one of the efforts to overcome the problems. In this case, Islamic religious education (PAI) subject must begin to improve and prepare itself to welcome and succeed the Merdeka Curriculum. The implementation of the Merdeka curriculum at SMA Negeri Jenggawah Jember is supported by several interesting issues to study, namely, the Full Day school program. In addition, it has a teacher learning community as well as a student learning community that support the implementation of the current curriculum in the Islamic Religious Education subjects, so that it expects to produce students with good morals and character. The research focuses in this study are: 1) How is the Planning of the Merdeka Curriculum as an effort to overcome the learning loss in Islamic Religious Education subject of X graders at SMA Negeri Jenggawah Jember? 2) How is the Implementation of the Merdeka Curriculum as an effort to overcome the learning loss in Islamic Religious Education subject of X graders at SMA Negeri Jenggawah Jember? 3) How is the Evaluation of the Merdeka Curriculum as an effort to overcome the learning loss in Islamic Religious Education subjects of X graders at SMA Negeri Jenggawah Jember? The research methods applied in this study are: 1) descriptive qualitative approach with case study research design. 2) Research setting. 3) The presence of researchers. 4) Research subjects: purposive sampling technique. 5) Source of data. 6) Data collection techniques: interviews, observation, and document review. 7) Data analysis through three steps: data reduction, data display, conclusion drawing and data verification. 8) Data validity with source and technique triangulation. 9) Research procedure. The research findings indicate that: 1) the planning process includes: PAI (Islamic Education) teachers preparing teaching modules for the independent curriculum, designing Islamic activity programs, and designing assessments based on the independent curriculum. 2) the implementation process includes: conducting active learning activities of the independent curriculum, implementing religious habituation activities, and PAI teachers meeting with parents regarding the implementation of the independent curriculum. 3) the evaluation process includes: evaluating the learning activities of the independent curriculum, evaluating the implementation of religious habituation activities based on the independent curriculum, and conducting joint evaluations with parents. Keywords: merdeka curriculum, learning loss, islamic religious education